Spatiotemporal localization of sex difference in plantar pressure distribution during self paced walking in healthy Japanese adults - Hirokazu Doi; Natsumi Furuta; Hyunchul Yoon; Kazuo Funato (PLoS ONE, 2026)
Objectives There is notable sex difference in the manner of locomotion, but researchers are yet to obtain the comprehensive information about the biomechanical difference in gait pattern between males and females. The present study aimed to investigate sex differences in plantar pressure distribution during self-paced walking using a cluster-based permutation approach. Method Plantar pressure data were collected from 24 healthy males and 68 healthy females using a pressure-sensor footplate. Group comparisons were conducted for basic gait parameters as well as pressure-related metrics, including maximum force, peak pressure, and contact area size. Additionally, time-series characteristics of total force were compared between sexes. A cluster-based permutation test was used to identify spatial and temporal regions with significant sex differences in plantar pressure distribution at high resolution. Results Analyses revealed that females exhibited shorter step durations and higher cadence compared to males, attributable in part to differences in the duration of the late stance phase. Females also demonstrated higher weight-normalized plantar pressures across most of the stance phase. Sex-specific differences in plantar pressure distribution were localized to the calcaneal and second metatarsal regions. Conclusion Spatially localized pattern of sex difference in the plantar pressure indicates that biomechanical factors may contribute to the sex difference in the incidence rates of clinical conditions such as stress fracture. There was also a hitherto unreported pattern of sex difference in the time-series of total force, that may be related to sex-specific strategy to keep a self-preferred walking speed.